2022
DOI: 10.3389/fpsyt.2022.839683
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Behavioral and Psychological Symptoms in Patients With Cognitive Decline Before and During the COVID-19 Pandemic

Abstract: ObjectivePreventive measures to limit the spread of COVID-19 are essential, but often cause social isolation, affecting the physical and mental health of older adults. Patients with dementia are likely to have worsening behavioral and psychological symptoms of dementia (BPSD) owing to pandemic restrictions. To examine this, we described BPSD before and during the COVID-19 pandemic.MethodsWe identified patients at a memory clinic in Japan between October 2018 and December 2019 (15 months before the pandemic beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Cagnin et al reported that sleep disturbance was the most common new BPSD during COVID-19, at a rate of 21.3% in dementia patients [ 17 ]. Our previous study also showed a higher frequency of sleep disturbance during COVID-19 than in normal times [ 18 ]. We showed here that maintaining good quality of sleep could help to reduce BPSD.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Cagnin et al reported that sleep disturbance was the most common new BPSD during COVID-19, at a rate of 21.3% in dementia patients [ 17 ]. Our previous study also showed a higher frequency of sleep disturbance during COVID-19 than in normal times [ 18 ]. We showed here that maintaining good quality of sleep could help to reduce BPSD.…”
Section: Discussionmentioning
confidence: 81%
“…We selected 1781 before-COVID-19 and 576 during-COVID-19 participants after excluding those with missing variables, including the primary outcome measure of the study, a score on the Dementia Behavioral Disturbance (DBD) scale [ 24 ]. The dataset used in this study was designed to be highly extensive before the COVID-19 period compared to the dataset used in our previous study [ 18 ], resulting in an increased number of participants. Independent researchers ensured that the same participants were not evaluated at the two time points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epidemic of COVID-19 has had a profound impact on the organization of clinical and social care activities for people with dementia and their caregivers. Undoubtedly, preventive measures to limit the spread of COVID-19 are essential, but in patients with dementia, they have often caused social isolation, and exacerbated behavioral and psychological symptoms of dementia (BPSD) [ 1 , 2 ] resulting in increased caregiver burden. [ 3 , 4 ] BPSD, also known as neuropsychiatric symptoms, represent a heterogeneous group of noncognitive symptoms, and behaviors that occur in people with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Mild cognitive impairment (MCI) is usually associated with cognitive impairment, which is seen with general age-related cognitive decline, but is not severe enough to lead to considerably impaired daily function (Stevens et al, 2022). Furthermore, the GRAPHICAL ABSTRACT | principal cognitive domain that could be afflicted refers to a decline in the capability to acquire raw information or recall stored information (Gatz et al, 2022;Kuroda et al, 2022). Clinically, age-related cognitive impairment represents the preclinical, transitional stage between healthy aging and dementia (Levey et al, 2021).…”
Section: Introductionmentioning
confidence: 99%